Rational Design of Near‐Infrared Aza‐Platinum‐Dipyrromethene‐Based Nanophototherapy Agent with Multistage Enhancement for Synergistic Antitumor Therapeutics. Issue 10 (16th August 2021) - Xu, Yunjian; Zhao, Menglong; Zhou, Yucheng; Wang, Jiawei; Li, Mingdang; Li, Feiyang; Lv, Wen; Liu, Shujuan; Zhao, Qiang
Abstract : The development of innovative synergistic phototherapy (SPT) agent with excellent photodynamic therapy (PDT) and photothermal therapy (PTT) effects for efficient antitumor is of great significance. However, the low photothermal conversion efficiency or low singlet oxygen yield of SPT agent during the phototherapy process will result in inefficient tumor therapy. Herein, a new near‐infrared (NIR) SPT agent based on aza‐platinum‐dipyrromethene dye (D‐3 ) with synergistic PDT and PTT effects is rationally designed and synthesized by the metallization and halogenation of aza‐dipyrromethene simultaneously. The introduction of iodine atoms and Pt(II) ion to aza‐dipyrromethene skeleton can not only effectively promote the excited electrons to undergo intersystem crossing process for improving singlet oxygen ( 1 O2 ) generation capability, but also inhibit radiative transition process for boosting photothermal conversion properties. For biological exploration, the biocompatible D‐3 nanomaterials (APIDNs) with excellent concentration‐dependent photoacoustic and photothermal properties are prepared, thus visibly guiding synergetic PDT and PTT effects for inhibiting the growth of tumor cells in vivo. This work demonstrates the superior therapy effects of APIDNs and its negligible dark cytotoxicity. The novel strategy reported in this work will offer a new way to design new‐generation NIR aza‐metal‐dipyrromethene‐based dyes for developing superior SPT agents. Abstract : A novel near‐infrared (NIR) absorbing iodine‐substituted Pt(II)‐chelated azadipyrromethene dye (D‐3 ) is developed for synergistic therapy. Heavy atom can not only promote singlet‐to‐triplet transition, but also prevent the radiative decay of azadipyrromethene skeleton for enhancing the photodynamic and photothermal effect. D‐3 exhibits excellent synergistic photodynamic and photothermal therapeutic effects in vitro and in vivo.